Avaliação de projetos para habitação de interesse social em foco na sustentabilidade - Vitorio Junior, Paulo Cezar (2020)
Considering importance of developing tools that support designers' decision-making, the objective of this thesis is to propose a model aimed to the identification the most sustainable alternative in single-family housing projects of social interest from the perspective of Life Cycle Thinking (LCT) and the Analytic Hierarchy Process (AHP) to be validated through the study of two projects. Project A and Project B are evaluated and, in the environmental dimension, the results show that Project A had greater environmental impacts and greater damage to the human health and to the availability of ecosystems and resources. In the social dimension, it was found that there are differences between the salaries paid by the construction supply chain and the Project B has better social characteristics than the Project A. The economic dimension pointed out that Project B is, economically, more attractive. Relating the results of the environmental, social and economic dimensions, through the combination of LCT and AHP, it was found that the Project B presents a combination of more sustainable characteristics than the Project A in the absolute majority of the results that were generated. Among the implications of the study carried out here is the advancement of sustainability applied to the construction of housing projects of social interest. The model presented here serves the basis for discussions about inclusion of the sustainability dimensions in construction and it shows to future professionals in the construction sector how the sustainability is relevant in the design of new structures. Finally, the proposed model aggregates data from the sustainability dimensions and allows the generation of sustainable decision-making scenarios involving measures of design and dimensioning of projects.